2019
DOI: 10.1161/hypertensionaha.118.11813
|View full text |Cite
|
Sign up to set email alerts
|

Immunoproteasome Subunit β5i Promotes Ang II (Angiotensin II)–Induced Atrial Fibrillation by Targeting ATRAP (Ang II Type I Receptor–Associated Protein) Degradation in Mice

Abstract: Atrial fibrillation (AF) is the most common type of cardiac arrhythmia and increases the risk of stroke, heart failure, and death. Ang II (angiotensin II) triggers AF, mainly through stimulation of the AT1R (Ang II type I receptor). The immunoproteasome is a highly efficient proteolytic machine derived from the constitutive proteasome, but the role it plays in regulating AT1R activation and triggering AF remains unknown. Here, we show that among the catalytic subunits, β5i (PSMB8) expression, and chymotrypsin-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
70
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(76 citation statements)
references
References 32 publications
6
70
0
Order By: Relevance
“…The immunoproteasome has critical functions in the regulation of protein degradation, immune cell homeostasis, oxidative stress and cell apoptosis [13,14]. Recently, we showed that the β2i and β5i subunits are involved in the development of cardiac remodeling, atrial fibrillation and retinopathy, thus extending previous knowledge about the immunoproteasome [15][16][17][18]. Notably, subunit β5i was upregulated in the shoulder areas of symptomatic carotid plaques as compared with non-symptomatic plaques, suggesting a correlation between β5i activity and plaque instability [19].…”
Section: Introductionsupporting
confidence: 55%
See 3 more Smart Citations
“…The immunoproteasome has critical functions in the regulation of protein degradation, immune cell homeostasis, oxidative stress and cell apoptosis [13,14]. Recently, we showed that the β2i and β5i subunits are involved in the development of cardiac remodeling, atrial fibrillation and retinopathy, thus extending previous knowledge about the immunoproteasome [15][16][17][18]. Notably, subunit β5i was upregulated in the shoulder areas of symptomatic carotid plaques as compared with non-symptomatic plaques, suggesting a correlation between β5i activity and plaque instability [19].…”
Section: Introductionsupporting
confidence: 55%
“…It has been demonstrated to be 20‐ to 40‐fold more selective for the β5i subunit than the constitutive β5 subunit and other immunoproteasome subunits . Increasing studies indicate that inhibition of the β5i subunit by PR‐957 is promising for the treatment of inflammatory and autoimmune diseases, with limited side effects . Here we extended the therapeutic potential of PR‐957 and immunoproteasome inhibition in atherosclerosis; however, this needs further verification in other animal models.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…After 3 weeks of treatment, the mice were anesthetized by an intraperitoneal injection of 2.5% tribromoethanol (0.02 mL/g; Sigma-Aldrich, St. Louis, MO, USA) [20]. At the end of Ang II infusion, intracardiac pacing was performed in mice through the insertion of an eight-electrode catheter (1.1F, octapolar EP catheter, Scisense, London, Ontario, Canada) via the jugular vein and its advancement into the right atrium and ventricle [20].…”
Section: Arrhythmia Inducibility and Durationmentioning
confidence: 99%